Cyclic Stable Matching Inspired Resource Provisioning for IoT-Enabled 5G Networks - Pratap A. (My University, 2025)
The next-generation wireless network is expected to be highly dense with a large number of heterogeneous Internet of Things (IoT) devices, working in co-operation with various Small Cell Access Points (SAPs) and Fog Servers (FSs) underlying cellular 5G infrastructure, altogether. The densely deployed 5G architecture is expected to fulfill the IoT's growing data demand in a feasible computational complexity. In this work, the resource provisioning mechanism in a heterogeneous 5G network is formulated to maximize the overall benefit of SAPs by selecting the most appropriate FSs for offloading the set of IoT tasks, as an NP-hard problem. Moreover, a Restricted Three-sided Matching with Size and Cyclic (R-TMSC) preference model is implemented to obtain a stable solution among IoTs, SAPs, and FSs underlying cellular 5G networks. Furthermore, the effectiveness of the proposed heuristic is shown through theoretical, experimental, and real-world data analysis. © 1967-2012 IEEE.